Looked after young people at risk of offending: their views of a mixed-gender placement. Issue 3 (2nd July 2016) - Copley, Jennifer; Johnson, Daniel
Abstract : Changes to residential child care placements, from single-gender to mixed-gender, highlighted limitations in research and guidance on the use and management of such placements. To begin consideration of this topic, this study explored experiences of young people living in a mixed-gender residential placement. Thematic analysis, using an inductive approach, elicited themes from interviews with seven girls and boys residing in one residential placement. The analysis highlighted one global theme – Gender should be considered, but is not a priority – and four organising themes – Mixed gender living is normal and beneficial; Living with other people is difficult, regardless of gender; Gender has its place and Other issues are more relevant . The analysis highlighted the relevance of gender focused research and exploring service users experiences. Exploring young people's experiences provided a starting point to the question of 'single-gender versus mixed-gender placements', providing vital insight into areas that warrant further exploration and areas of development that may improve the management of mixed-gender residential placements.